High frequency CMOS precision full-wave rectifier circuit - Guntapong, Rojanakorn; Riewruja, Vanchai; Fongsamut, Chalermpan; Kaewpoonsuk, Anucha (My University, 1999)
A CMOS integrable circuit technique for the realization of full-wave precision rectifier circuit, which operates throughout in the current domain, is presented. The circuit achieves a wide dynamic range and a wide-band capability. The rectifying characteristic of the circuit exhibits a low distortion in the output signal at low level input signal, Simulation results demonstrating the circuit performance are included.